2009
DOI: 10.1099/mic.0.029546-0
|View full text |Cite
|
Sign up to set email alerts
|

Low pH regulates the production of deoxynivalenol by Fusarium graminearum

Abstract: Fusarium graminearum, which causes the globally important head blight disease of wheat, is responsible for the production of the harmful mycotoxin deoxynivalenol (DON) in infected grain. The production of DON by F. graminearum occurs at much higher levels during infection than during axenic growth, and it is therefore important to understand how DON production is regulated in the fungus. Recently, we have identified amines as potent inducers of in vitro DON production in F. graminearum. Although amines strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 36 publications
8
99
1
1
Order By: Relevance
“…4A). This observation is consistent with previous studies (Gardiner et al, 2009b, Merhej et al, 2010. However, the FgDPac1 strain showed a behaviour similar to the wild-type strain since the toxin was produced under acidic pH conditions (MSM and BMS3) but was still not detected under neutral pH (BMS6.5).…”
Section: Fgpac1 Mutations Are Able To Affect Trichothecene Productionsupporting
confidence: 93%
See 1 more Smart Citation
“…4A). This observation is consistent with previous studies (Gardiner et al, 2009b, Merhej et al, 2010. However, the FgDPac1 strain showed a behaviour similar to the wild-type strain since the toxin was produced under acidic pH conditions (MSM and BMS3) but was still not detected under neutral pH (BMS6.5).…”
Section: Fgpac1 Mutations Are Able To Affect Trichothecene Productionsupporting
confidence: 93%
“…A variety of amines were also identified as potent inducers of DON production (Gardiner et al, 2009a). In addition to those factors, it has been recently reported that low extra-cellular pH both promotes and is required for toxin production in F. graminearum (Gardiner et al, 2009b;Merhej et al, 2010). However, the mechanism by which pH regulates trichothecenes remains unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Reduced nitrogen sources such as the amines putrescine and arginine in combination with a low pH are also excellent in vitro inducers of DON production (Gardiner et al, 2009a(Gardiner et al, , 2009cMerhej et al, 2011). Putrescine and arginine accumulate in F. graminearum infected wheat heads (Gardiner et al, 2010) and their biosynthesis is known to be upregulated in plants during defence responses (Haggag and Abd-El-Kareem, 2009;Walters, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…graminearum (Gardiner et al, 2009c). Thus, DON production and fusatin production in F. pseudograminearum seem to share regulatory networks, as both are induced by asparagine, however their regulatory networks also seem to diverge at some point, as more DON is produced in citrulline than in asparagine, but no fusatin could be detected in citrulline.…”
Section: Cellular Developmental Changes and Subcellular Reorganizatiomentioning
confidence: 94%
“…Reduced nitrogen sources such as the amines putrescine and arginine in combination with a low pH are also excellent in vitro inducers of DON production (Gardiner et al, 2009a(Gardiner et al, , 2009cMerhej et al, 2011). Putrescine and arginine accumulate in F.…”
Section: Introductionmentioning
confidence: 99%